Mechanical and Chemical Processing of Wool Fiber Technology - O. A. Toshbekov.; M. K. Urozov.; E. N. Juraqulov.; S. A. Raximqulova (International Journal on Integrated Education, 2021)
This article discusses the methods of mechanical and chemical processing of wool fiber technology, as well as their application in practice.